Advanced Technologies in Bio/Hydrometallurgy for Recovery and Recycling of Metals - Stefano Ubaldini (Metals, 2023)
Studying innovative and sustainable technologies for the recovery and reuse of raw materials (RMs) from primary and secondary resources is fundamental for economic and industrial development in compliance with environmental protection and in the context of a circular economy [...]